Enhancement of Nuclear Fusion in Plasma Oscillation Systems - Alfred YiuFai Wong; Chun-Ching Shih (Plasma, 2022)
Concepts of dynamic oscillations of positive and negative ions to enhance fusion reactions are examined in this paper. Collective oscillations of positive and negative ions produce large oscillating electrostatic fields and could provide a significant reduction of the Coulomb potential barrier between the two interacting species (such as hydrogen anion H− and B+ in the hydrogen-boron fusion reaction). The negative hydrogen ions can be produced by populating low-temperature electrons around the neutral hydrogen atoms in a rotation chamber. The existence of H− ensures the stability of the plasma and the effectiveness of fusion interactions between H− and B+. In this paper, theoretical analyses of such oscillations systems will be presented and the conditions for fusion enhancement are discussed.